A Preliminary Study of Extraction and Characterization of Nanocrystalline Cellulose (NCC) from Ramie Fiber - K Kusmono; Muhammad Waziz Wildan; Mochammad Noer Ilman (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Nanocrystalline cellulose (NCC) is today’s one of rapidly growing nanocomposite reinforcing materials. This is thanks to some advantages that come with it over anorganic nanocomposite reinforcing materials, for example, nanoclay, nanosilica, nanoalumina, carbon nanotubes, among others. Some of the advantages of NCC are environment-friendliness due to being organic-compound-based, high mechanical property, and easy manufacturing. NCC can be extracted from natural cellulose sources, such as natural fiber, wood, and animals. One of the natural fibers rich in cellulose content, in this case around 80%, is fiber of ramie which is ubiquitous in Indonesia. It is well known that the acid hydrolysis method is an easy route to NCC fabrication. A number of chemical treatments like de-waxing, bleaching, and alkaline treatment are typically performed prior to acid hydrolysis process. The effect of such chemical treatments as precursors of alkaline hydrolysis on ramie fiber characteristics was investigated in this research. Firstly, ramie fiber was cut 1 cm in size, then grinded and sieved. The fiber was then subjected to de-waxing process by adding it into a toluene-ethanol solution (1:2). Then, it was submitted to bleaching with 0.7% sodium chlorite (NaClO2) solution at 75 °C for 1 hour. Lastly, the fiber was subjected to an alkaline treatment in 2% NaOH solution for 2 hours. Characterization with FT-IR, XRD, and TGA of the fiber which had underwent a number of surface treatments was conducted. Results show that the chemical treatments had successfully removed amorphous components like lignin and hemicellulose from the ramie fiber. Chemical treatments were proven able to increase the crystallinity index and thermal stability of ramie fiber.